Extracellular biosynthesis of platinum nanoparticles using the fungus fusarium oxysporum - Syed, Asad; Ahmad, Absar (Colloids and Surfaces B-Biointerfaces, 2012)
Nanoscience is a blooming field and promises a better future. In order to fabricate nanoparticles in an eco-friendly and inexpensive manner, significant efforts are being made to replace the chemical and physical methods currently being used with the biological methods. Chemical methods are toxic while the physical ones are very expensive. Biological methods, apart from being cost-effective, also provide protein capped nanoparticles which are thus very stable, have good dispersity and do not flocculate, and may find use in various applications. The present work emphasizes on platinum nanoparticles synthesis protocol which occurs at ambient conditions. The fungus Fusarium oxysporum when incubated with hexachloroplatinic acid (H2PtCl6) in ambient conditions reduces the precursor and leads to the formation of stable extracellular platinum nanoparticles. The biosynthesis of platinum nanoparticles was monitored by UV-visible spectroscopy and these nanoparticles were completely characterized by transmission electron microscopy (TEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). The nanoparticles are in the size range of 5-30 nm and are stabilized by proteins present in the solution. The reduction process is believed to occur enzymatically, thus creating the possibility of a rational, fungal-based method for the synthesis of nanoparticles over a wide range of chemical compositions. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Biosynthesis; Fungus; Nanoparticles; platinum

Extracellular biosynthesis of CdTe quantum dots by the fungus fusarium oxysporum and their anti-bacterial activity - Syed, Asad; Ahmad, Absar (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2013)
The growing demand for semiconductor [quantum dots (Q-dots)] nanoparticles has fuelled significant research in developing strategies for their synthesis and characterization. They are extensively investigated by the chemical route; on the other hand, use of microbial sources for biosynthesis witnessed the highly stable, water dispersible nanoparticles formation. Here we report, for the first time, an efficient fungal-mediated synthesis of highly fluorescent CdTe quantum dots at ambient conditions by the fungus Fusarium oxysporum when reacted with a mixture of CdCl2 and TeCl4. Characterization of these biosynthesized nanoparticles was carried out by different techniques such as Ultraviolet-visible (UV-Vis) spectroscopy, Photoluminescence (PL), X-ray Diffraction (XRD), X-ray Photoelectron spectroscopy (XPS), Transmission Electron Microscopy (TEM) and Fourier Transformed Infrared Spectroscopy (FTIR) analysis. CdTe nanoparticles shows antibacterial activity against Gram positive and Gram negative bacteria. The fungal based fabrication provides an economical, green chemistry approach for production of highly fluorescent CdTe quantum dots. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: antibacterial activity; Biosynthesis; CdTe; Fungus; Nanoparticles

Extracellular biosynthesis of metal sulfide nanoparticles using the fungus fusarium oxysporum - Senapati, Satyajyoti; Syed, Asad; Khan, Shadab; Pasricha, Renu; Khan, Mohammad Islam; Kumar, Rajiv; Ahmad, Absar (Current Nanoscience, 2014)
The development of reliable, eco-friendly processes for the synthesis of nanomaterials is an important aspect of nanotechnology. One approach that shows immense potential is based on the biosynthesis of nanoparticles using microorganisms such as bacteria. In this report, we demonstrate the extracellular biosynthesis and complete characterization of metal sulfide (PbS, ZnS, MnS and NiS) nanoparticles using fungus, Fusarium oxysporum. We observed that the exposure of aqueous solution of 1 mM metal sulfate to fungus Fusarium oxysporum resulted in the formation of highly stable technologically important metal sulfide semiconductor nanoparticles. Fusarium oxysporum synthesizes lead sulfide and zinc sulfide nanoparticles of fractal type structure whereas manganese sulfide and nickel sulfide nanoparticles are of variable polydispersed morphology. The variable morphology may be due to the dissimilar interaction of metal sulfide nanoparticles with capping proteins secreted by the fungus in solution. The nanoparticles solution is found to be extremely stable with little evidence of aggregation even after a month of storage. The long term stability of the nanoparticles is due to the proteins secreted by fungus in the nanoparticle solution which bind to the surface of the nanoparticles and thus prevent aggregation.
Keywords: Biosynthesis; enzymes; fungi; metal sulfide; Nanoparticles